Tinjauan Terhadap Hukum Agraria Maritim: Sumber Daya Alam Dan Regulasi Di Kawasan Laut - Revhan Sakti Pratama; Dimas Bima Saputra; Dewi Haryanti; Endri Endri (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2024)
The term "agraria" is used in the Indonesian government administration to describe "land", both agricultural and non-agricultural land. For example, by Decree No. 26 of 1988, the National Farming Authority was established as the Director General of Agriculture of the Department of Home Affairs. Agrarian law (Agrarisch Recht) in the administrative district of the Dutch Indian government is confined to a set of legislative regulations that provide a legal basis for the rulers to implement agricultural policy. In this study, the method of normative analysis is used. Normative law research or library research is a type of research that studies documents using various secondary data such as laws. Within Indonesia there are a variety of natural resources, including fishing, mangrove forests, while the regulations that govern the Indonesian seas vary in various aspects, among others: the Persian Sea, Wiayah Sea, Continental Land, Exclusive Economic Zone, Additional Zone, Overseas Sea. In conclusion, maritime agrarian law is very important in understanding and utilizing natural resources related to land and waters. Marine natural resources play a vital role inining the balance of global ecosystems as well as providing economic benefits to communities. Within the framework of sustainable development, we are faced with the great challenge of understanding and using marine agricultural resources wisely.